Association of Psb28 and Psb27 Proteins with PSII-PSI Supercomplexes upon Exposure of Synechocystis sp. PCC 6803 to High Light - Bečková, Martina; Gardian, Zdenko; Yu, Jianfeng; Konik, Peter; Nixon, Peter J; Komenda, Josef (Molecular plant, 2017)
Formation of the multi-subunit oxygen-evolving photosystem II (PSII) complex involves a number of auxiliary protein factors. In this study we compared the localization and possible function of two homologous PSII assembly factors, Psb28-1 and Psb28-2, from the cyanobacterium Synechocystis sp. PCC 6803. We demonstrate that FLAG-tagged Psb28-2 is present in both the monomeric PSII core complex and a PSII core complex lacking the inner antenna CP43 (RC47), whereas Psb28-1 preferentially binds to RC47. When cells are exposed to increased irradiance, both tagged Psb28 proteins additionally associate with oligomeric forms of PSII and with PSII-PSI supercomplexes composed of trimeric photosystem I (PSI) and two PSII monomers as deduced from electron microscopy. The presence of the Psb27 accessory protein in these complexes suggests the involvement of PSI in PSII biogenesis, possibly by photoprotecting PSII through energy spillover. Under standard culture conditions, the distribution of PSII complexes is similar in the wild type and in each of the single psb28 null mutants except for loss of RC47 in the absence of Psb28-1. In comparison with the wild type, growth of mutants lacking Psb28-1 and Psb27, but not Psb28-2, was retarded under high-light conditions and, especially, intermittent high-light/dark conditions, emphasizing the physiological importance of PSII assembly factors for light acclimation.
Keywords: bakteriální proteiny; Protein Binding; Photosystem II Protein Complex; světlo; Synechocystis; Psb28 proteins; photosystem I and II; vazba proteinů; Mutation; mutace; Light; Photosystem I Protein Complex; Bacterial Proteins; fotosystém I (proteinový komplex); fotosystém II (proteinový komplex)